NCCIH Priorities for Natural Products Research - Still, Patrick; Chen, Wen; Weber, Wendy; Hopp, D. Craig (Planta Medica, 2022)
The National Center for Complementary and Integrative Health (NCCIH) is the lead agency within the U. S. federal government for complementary and integrative health research, which includes natural products. Although NCCIH is one of the smaller components of the National Institutes of Health (NIH), NCCIH funds a disproportionately high percentage of natural products research at NIH. This stems from NCCIH being the only NIH grant issuing component that includes natural products as an explicit part of its mission. This perspective provides an overview of the NCCIH mission and summarizes NCCIH funding priorities for natural products research across basic and mechanistic as well as clinical sectors. These priorities are guided by the recently released NCCIH strategic plan. A primary element of this new plan is a focus on whole person health instead of the frequent focus on the treatment of diseases. The NCCIH focus on whole person health includes how natural products and multicomponent therapeutic approaches, which often include natural products, can help move individuals towards health restoration and promotion.
Keywords: pharmacognosy; pharmacology; clinical studies; natural products analysis; molecular targets and activities